One pot synthesis of poly m-toluidine incorporated silver and silver oxide nanocomposite as a promising electrode for supercapacitor devices - Doaa Essam; Ashour M. Ahmed; Ahmed A. Abdel-Khaliek; Mohamed Shaban; Mohamed Rabia (Scientific Reports)
Abstract The design and fabrication of novel electrodes with strong electrochemical responses are crucial in advanced supercapacitor technology. In this study, a poly(m-toluidine)/silver-silver oxide (PMT/Ag-Ag2O) nanocomposite was prepared using the photopolymerization method. Various characterization techniques were employed to analyze the prepared nanomaterials. The resulting structure of Ag-Ag2O minimizes ion diffusion distances, increases active sites, and accelerates redox reactions. The electrochemical response of PMT and PMT/Ag-Ag2O electrodes was evaluated in three different electrolyte solutions (Na2SO4, H2SO4, and HCl). The specific capacitance of PMT/Ag-Ag2O nanocomposite was found to be higher than that of PMT alone. Among the tested electrolytes, HCl exhibited the highest specific capacitance of 443 F g−1 at a gravimetric current density of 0.4 A g−1, surpassing H2SO4 (104 F g−1) and Na2SO4 (32 F g−1). Also, the PMT/Ag-Ag2O nanocomposite has demonstrated good cycling stability. It exhibited a high specific power density of 156 W Kg−1 and a specific energy density of 1.8 Wh Kg−1. These results highlight the potential of the prepared PMT/Ag-Ag2O nanocomposite as a nanoelectrode material for high-performance supercapacitors.